IDEAS RELIGIOSAS DE EURÍPIDES A TRAVÉS DE SUS OBRASQ - Muñoz Llamosas, Virginia (Myrtia, 2002)
In this article we consider the religious ideas that Euripides shows through his plays, paying special attention to their evolution and how the author reflects the ideological polemics of the fifth century Athens.